Mineralogical determination, isotopic compositions and Strontium isotope ratios from an outcrop near Kardio village, Xigaze in Tibet - Hongpeng Tong; Qinxian Wang; Jörn Peckmann; Yuncheng Caoa; Linying Chena; Weide Zhou; Duofu Chen (PANGAEA, 2017)
Seep carbonates provide excellent records of past seepage activities, and have been commonly considered to preserve primary, unaltered stable carbon isotope signatures. However, late diagenetic reactions may overprint original isotopic compositions, but the mode and effect of such alterations are poorly understood. In particular, there are significant uncertainties regarding how carbon and strontium isotopic compositions of seep carbonates respond to diagenesis. This study reports recently discovered Cretaceous hydrocarbon-seep deposits from the Yarlung-Zangbo Suture Zone, Tibet, China that have experienced substantial diagenetic alteration that is shown by recrystallization and secondary veins. Unitary linear recursive analysis was applied to d13C values and 87Sr/86Sr ratios of the seep carbonates to evaluate the degree of secondary modification and to quantitatively constrain the compositions of primary carbonates and late diagenetic fluids. The d18O values range from - 11.8 per mil to - 2.2 per mil, d13C values from - 34.1 per mil to - 12.9 per mil and 87Sr/86Sr ratios from 0.706221 to 0.706808. The heterogeneity in isotopic compositions and the observation that the most negative d18O values occur in samples with the most extensive recrystallization indicate significant and spatially heterogeneous modification of isotope compositions during late diagenesis. The linear correlations between d13C values and d18O values for matrix micrites (R2 = 0.54), and between bulk carbonate 87Sr/86Sr ratios and d18O values (R2 = 0.85) are best explained by burial diagenetic overprinting of oxygen, strontium, and even carbon isotopic compositions rather than by meteoric water hypergenesis. Extrapolated values of d13C and ratios of 87Sr/86Sr against a d18O value of - 2 per mil (average value of calcite precipitated in isotopic equilibrium with coeval Cretaceous seawater) that would characterize the primary carbonate, give an end member d13C value of - 34 per mil and an end member 87Sr/86Sr ratio of 0.7072. The end member isotopic values obtained by this extrapolation suggest that the primary seep carbonates with low d13C values and high 87Sr/86Sr ratios were formed by anaerobic oxidation of methane near the seafloor. In contrast, the measured d18O values and 87Sr/86Sr ratios reflect late diagenetic fluids represented by burial pore water characterized by a low 87Sr/86Sr ratio and high temperature. Our findings reveal that d13C values can only be moderately and 87Sr/86Sr ratios can be significantly altered during late diagenesis, and show that it is possible to quantitatively assess the primary composition of diagenetically altered seep carbonates.
Supplement to: Tong, H et al. (2016): Diagenetic alteration affecting d18O, d13C and 87 Sr/ 86 Sr signatures of carbonates: A case study on Cretaceous seep deposits from Yarlung-Zangbo Suture Zone, Tibet, China. Chemical Geology, 444, 71-82, https://doi.org/10.1016/j.chemgeo.2016.10.003